A MULTIDISCIPLINARY APPROACH TO ISLAMIC STUDIES: INTEGRATION OF EDUCATION, SOCIAL, AND RELIGIOUS CULTURE IN THE MODERN ERA - Zulham Ependi Siregar; Rahman Husein; Saiful Salim; Lestari Annisa; Mohd Rafiq (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study examines a multidisciplinary approach in Islamic studies as an effort to understand Islamic teachings more comprehensively through the integration of educational, social, and religious-cultural perspectives in the modern era. The study is motivated by increasingly complex social developments that require an approach beyond normative religious understanding by considering social and cultural contexts. This research employs a qualitative method using a literature review by collecting data from books, scientific journals, and relevant academic articles. The findings indicate that a multidisciplinary approach in Islamic studies broadens the understanding of Islamic teachings, strengthens the relevance of Islamic education to social life, and encourages adaptive and contextual religious practices. This approach also contributes to the development of Islamic studies that are more open, integrative, and responsive to contemporary social change.